INFLUENCE OF JOB SENIORITY, HAND HYGIENE EDUCATION, AND PATIENT-TO-NURSE RATIO ON HAND DISINFECTION COMPLIANCE - Budoor Obiad Aldhafeeri, Koloud Ashwy Aldhafeer, Mona Obiad Aldhafeeri, Shaikaha Aday Al Dhaferi, Maryam Fazzaa Aldafeeri, Albandary Nawaf Alwjaan, (Chelonian Research Foundation, 2022)
Despite proven effectiveness, suboptimal hand hygiene compliance among hospital nurses persists globally. This concurrent embedded mixed methods study examined influences on hand disinfection practices among 322 nurses across 10 hospitals in Saudi Arabia. Direct observation showed an overall compliance rate of 65%. Qualitative interviews with 20 nurses revealed ingrained habits, workload, forgetfulness, and environmental barriers challenged adherence. Multivariate analysis indicated newer nurses, recent education, and lower patient ratios had higher compliance. Adherence was 13% higher during patient room exit versus entry. Thematic results emphasized the need to foster motivational strategies and user-centered design. A multidimensional approach addressing behavioral, educational, workload, and environmental factors across nurse experience levels is warranted to enhance hand hygiene compliance and reduce preventable hospital-acquired infections in Saudi Arabia. Keywords: hand hygiene, disinfection, hospital, nurses, mixed methods, Saudi Arabia